Ontological dimension of the management of national secondary education from the optic of corporate social responsibility (Gestión y Gerencia, 2021)
This essay theoretically analyzes the ontological dimension of management carried out in Venezuelan secondary education from the perspective of Corporate Social Responsibility. The objectives are aimed at reviewing its application in that specific context, to explore whether its application responds to the intention from the context of a Socially Responsible educational management or is seen as an organization competitiveness strategy. The methodology deals with the bibliographic review allowing to assume a position close to the subject, therefore it cannot refer to the ontological dimension of that management with identical connotations as it can be done in the business area. It is in the context of modernity, when the possibility of managing school and education as the same organization was effectively thought of, but reality has shown, in a particular way, that educational management requires the use of competitive strategies. In the short term, masked in a real and effective commitment of education with society to increase its quality and social legitimacy. From this point of view, ethical and moral values, guarantors of human freedom, must be part of the deliberate choices or strategic preferences of that educational management.
Keywords: Ontological dimension; high school education management; Corporate Social Responsibility